2022
DOI: 10.2196/29537
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Technology-Mediated Behavioral Lifestyle Interventions With Different Levels of Coach and Peer Support Among Latino Men: Comparative Study Within One Arm of a Randomized Controlled Trial

Abstract: Background Although Latino men have the highest prevalence (45%) of obesity among all men in the United States, traditional weight loss interventions have not effectively engaged this hard-to-reach and diverse group. Offering choices among technology-mediated weight loss interventions may offer advantages. Objective The aim of this study is to examine Latino men’s preferences among 3 weight loss intervention options. We also examined whether attendance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In the previously mentioned ANIMO study, where mHealth technology was not included, the mean weight loss in the GCSWLI at week 12 was −6.3 kg (95% CI −8.1 to −4.4 kg), and it was maintained at week 24 (−6.4 kg, 95% CI −8.6 to −4.3 kg) [ 21 ]. More recently, Rosas et al [ 14 ] conducted a study focusing on a choice-based technology-mediated lifestyle intervention for 200 Latino men. It compared 3 weight loss intervention options (videoconference, web-based videos, and in person) based on participants’ choices.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previously mentioned ANIMO study, where mHealth technology was not included, the mean weight loss in the GCSWLI at week 12 was −6.3 kg (95% CI −8.1 to −4.4 kg), and it was maintained at week 24 (−6.4 kg, 95% CI −8.6 to −4.3 kg) [ 21 ]. More recently, Rosas et al [ 14 ] conducted a study focusing on a choice-based technology-mediated lifestyle intervention for 200 Latino men. It compared 3 weight loss intervention options (videoconference, web-based videos, and in person) based on participants’ choices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, attendance at individual counseling sessions for ANIMO was 77% and was 75% (144/192) for this mHealth study. Rosas et al [ 14 ] observed that the mean number of sessions attended out of 12 weeks was 10.9 (SD 2.6) for the videoconference sessions and 9.7 (SD 4.3) for in-person sessions. Continued efforts to examine which aspects of these studies, including delivery options and which intervention components (eg, mHealth) influence study effectiveness, are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations